Perceptions of food availability and self-reported dietary intake in urban Costa Rican women: A Pilot Study - Bekelman, Traci A. (Universidad de Costa Rica, 2016)
Background: Food availability and dietary intake are thought to contribute to rising obesity among women of low socioeconomic status in Latin America. In Costa Rica, few studies have investigated food availability, dietary intake, or how they vary by SES. Objectives: The purpose of this study in San José, Costa Rica was to (1) evaluate women’s perceptions of food availability and, (2) describe dietary intake in women from low- and high-SES areas of the city. Methods: Thirty non-pregnant, non-lactating women between 25 and 50 years were recruited in March 2013 from a low- and high-SES canton. Structured, qualitative interviews assessed perceptions of food availability in 17 of the 30 women. Quantitative 24-hour dietary recalls assessed dietary intake in all 30 women. Results: Many women from the low-SES canton reported that they would include more chicken and fish in their diet if cost were not a barrier. Protein intake as a proportion of total energy intake was significantly greater in women from the high- versus low-SES canton (17% SD=5 vs. 13 SD=3, p = 0.02). Protein intake from animal source foods was significantly greater in women from the high-SES canton (38 g SD=22 vs. 21 SD=11, p = 0.02). Conclusion: Protein intake was greater in high-SES women and this may be due to the perceived cost of animal source foods.